Pete the cat : too cool for school - Dean, Kimberly; Dean, James (New York : Harper, 2014)
"Pete the cat can't decide what to wear to look cool at school. Pete learns it's not what you wear, but how you wear it that makes you cool"--Cover.
Keywords: Children's stories